An analytical solution of thermo-elastic behaviour of multi-layered cylindrical wellbore for underground hydrogen storage - Tan, Kok Hee (2019)
The energy produced by renewable resources is playing an increasing role. The random and inconsistent nature of renewable sources such solar and wind has made the hydrogen to be derived and to be stored. Hydrogen being an energy carrier that can be converted to mostly electrical energy when the need arise. Large-scale storage of hydrogen is mainly obtained by storing it underground, especially by making use of the depleted gas-wells previously storing oil and gas. The study about multilayered wellbore of oil and gas reservoirs has attracted numerous researchers. This research is targeted to investigate the thermo-elastic behaviour of the multi-layer cylindrical wellbore of the gas-well for the underground hydrogen storage through analytical solution. Such analytical solution shall enable further investigation of the strength of the wellbore to be carried out as the integrity of the well has to be determined in order the safe operation of the underground storage facility could be maintained. In this research project, a stable analytic solution to predict the thermomechanical stress-strain behaviour of the multi-layer wellbore when subject to thermal and pressure loading is developed. The analytical solution derived is then proposed to be verified by using finite element analysis on Ansys which is also constructed in this research. The analytical solution is then applied to two-layer and four-layer gas-well models with appropriate underground geometry and material models with corresponding boundary conditions. The results from analytical solution that expressed in terms of the temperature distribution, radial, axial and circumferential stress distributions are found to be in order as they are all in line with those results from the validating finite element analysis. As for the effect of number of layers onto the stress distribution, the results exhibited a very clear difference in the circumferential stress distribution with the circumferential stress of 2 MPa at inner radius of first layer of the four-layered model as compare to 30 MPa at inner radius of first layer of the two layered model. In summary, the results obtained from analytical solution are well validated by the finite element analysis thus gives conclusions that the analytical solution derived are applicable to estimate and study the thermo-elastic behaviour of multi-layered cylindrical wellbore for underground hydrogen storage.